Instructor's guide for Case studies for teaching special needs and at-risk students - Buzzell, Judith (Delmar Publishers, 1994)
This text provides lively and instructive true-life cases of challenging situations faced by teachers in traditional and special education classrooms. This case format is based upon the Harvard Business School case-based approach to instruction in which educational students decision-making skills are developed through analysis of practicing professionals problems portrayed in case studies